2018
DOI: 10.1063/1.4993101
|View full text |Cite
|
Sign up to set email alerts
|

Determination of coal ash content by the combined x-ray fluorescence and scattering spectrum

Abstract: An alternative method is proposed for the determination of the inorganic constituent mass fraction (ash) in solid fuel by the ratio of Compton and Rayleigh X-ray scattering peaks I/I subject to the iron fluorescence intensity. An original X-ray optical scheme with a Ti/Mo (or Sc/Cu) double-layer secondary radiator allows registration of the combined fluorescence-and-scattering spectrum at the specified scattering angle. An algorithm for linear calibration of the Compton-to-Rayleigh I/I ratio is proposed which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…A detailed description of the method for preparing films is given in [7]. The elemental composition of the targets and films was controlled by X-ray fluorescence analysis [9]. The identification of the quasicrystalline phase and the determination of its quasicrystallinity parameter aq were carried out according to J.W.…”
Section: Objects and Methodsmentioning
confidence: 99%
“…A detailed description of the method for preparing films is given in [7]. The elemental composition of the targets and films was controlled by X-ray fluorescence analysis [9]. The identification of the quasicrystalline phase and the determination of its quasicrystallinity parameter aq were carried out according to J.W.…”
Section: Objects and Methodsmentioning
confidence: 99%
“…Zhang et al 37 measured heavy metals such as Hg, Pb, Cr and other elements such as Ti, Fe and Ca in pulverized coal using an online XRF analyzer, and the relative standard deviations (RSDs) obtained from the measurements were all less than 7.74%. Although XRF is effective for the measurement of ash-forming elements and ash content in coal, its fluorescence yield for light elements is low, and it is usually not suitable for analyzing elements 38 with atomic numbers less than 11, so it cannot be used to analyze the content of organic elements such as C and H that are positively related to the calorific value 39 of coal.…”
Section: Introductionmentioning
confidence: 99%
“…The uniqueness of this method lies in the fact that it is suitable for the rapid identification of elements with a small atomic number down to hydrogen ( Z = 1) with tables . Recently, the ratio of Compton and Rayleigh scattering intensities has been used in solving both fundamental problems of determining the effective atomic number and mass absorption coefficients and applied problems of adjusting the composition in the XRF analysis, and also for determining the fraction of light elements in the sample bulk and the distribution of light elements along its depth . In our previous work, it was shown that the trueICIR dependence on the atomic number can be used as a calibration function for identification of single‐component and binary materials in certain ranges of effective atomic numbers Zeff .…”
Section: Introductionmentioning
confidence: 99%